IPS Empress 도재관의 파절강도 : 상악 견치에서 절단연 삭제량과 축면 경사도에 따른 영향 - 신동국; 강한중; 박용석; 박광수; 동진근; Shin Dong-Kuk; Kang Han-Joong; Park Yong-Suck; Park Kwang-Soo; Dong Jin-Keun (Taehan Chikwa Poch'ol Hakhoe chi, 2005)
Purpose. The purpose of this study was to compare the fracture strength of the IPS Empress ceramic crown according to the incisal reduction (2.0mm, 2.5mm, 3.0mm) and axial inclination ($4^{°}$, $8^{°}$, $12^{°}$) of the upper canine. Material and methods. After 10 metal dies were made for each group, the IPS Empress ceramic crowns were fabricated and each crown was cemented on each metal die with resin cement. The cemented crowns mounted on the testing jig were inclined 30 degrees and the universal testing machine was used to measure the fracture strength. Results. 1. The fracture strength of the ceramic crown with 3.0mm depth and $12^{°}$ inclination was the highest (839N) Crowns of 2.0mm depth and $12^{°}$ inclination had the lowest strength (559N). 2. There was no significant difference in the fracture strength by axial inclination in the same incisal reduction group. 3. The fracture mode of the crowns was similar. Most of fracture lines began at the loading area and extended through proximal surface perpendicular to the margin irrespective of incisal reduction.